Pengaruh Aromaterapi Lavender Terhadap Kecemasan Ibu Hamil Trimester III Di Puskesmas Merakurak - Vivi Nur Aromatika; Aris Puji Utami (Pusat Riset dan Inovasi Nasional, 2024)
Anxiety of pregnant women is something that can affect the development of the fetus and the psychology of pregnant women. One way to overcome anxiety is by giving lavender aromatherapy. Lavender is a plant that is often used as aromatherapy because it can provide calming, relaxing benefits. This study aims to determine whether there is an effect of lavender aromatherapy on the anxiety of pregnant women in the third trimester.The research design used in this research is quantitative quasi experiment (one group pre-post test design). This study has an independent variable of lavender aromatherapy and a dependent variable of third trimester pregnant women's anxiety. The sample in this study was 16 third trimester pregnant women using random sampling technique. The data collection method for the anxiety variable is using the Perinatal Anxiety Screening Scale (PASS) questionnaire.The results of the study showed that pregnant women in the third trimester, before being given lavender aromatherapy, experienced the most severe levels of anxiety, but after being given lavender aromatherapy, their anxiety levels decreased. The results of the research carried out were analyzed using the Wilcoxon test with a significance level of α = <0.05, with a value of ρ = 0.002 < 0.05, the result was a value of Asymp sig (2-tailed) = 0.002 which shows that the influence between the two variables is in the strong category. in a positive direction. Based on the data analysis, it can be concluded that lavender aromatherapy has an effect on the level of anxiety in third trimester pregnant women in the Merakurak Community Health Center Work Area.The findings of this research can be a source of learning and provide information regarding non-pharmacological therapy to reduce anxiety levels in third trimester pregnant women using lavender aromatherapy. The author also hopes that this research can be used as a basis for conducting further research using different designs.